PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPAS KELAS IV SD NEGERI 175822 MATIO - Sihombing, Suster Margaretta; Antonius Remigius Abi; Patri Janson Silaban; Regina Sipayung; Irmina Pinem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the cooperative learning model type Mind Mapping on the learning outcomes of students in the IPAS subject in Grade IV of SD Negeri 175822 Matio Academic Year 2024/2025. This study employs a quantitative method, with the research population consisting of all fourth-grade students at SD Negeri 175822 Matio and a sample size of 22 students selected using the boring sampling technique (total sampling). Data on the Mind Mapping learning model were obtained from a questionnaire distributed to students, while student learning outcomes were derived from pretest and posttest scores for the 2024/2025 academic year. The results of this study indicate that student learning outcomes using the Mind Mapping model fall into the good category, with an average Posttest score of 78.27 and an average questionnaire score of 73,82. Furthermore, the hypothesis testing results show a t-value of 4,557, while the t-table value is 2,085. Therefore, it is proven that Ho is rejected and Ha is accepted. Through the t-test, it can be concluded that there is a significant positive effect between the Mind Mapping cooperative learning model and student learning outcomes in the IPAS subject for fourth-grade students at SD Negeri 175822 Matio in the 2024/2025 academic year.